An Inspector Calls - "Priestley, J.B" (Heinemann Educational Books: Clay, 1988)
A three-act drama, which takes place on a single night in April 1912, focusing on the prosperous upper middle-class Birling family, who live in a comfortable home in the fictional town of Brumley, "an industrial city in the north Midlands". The family is visited by a man calling himself Inspector Goole, who questions the family about the suicide of a young working-class woman, Eva Smith (also known as Daisy Renton)"--Wikipedia.org
Keywords: English drama 20th century